Pengaruh Budaya Organisasi, Kepuasan Kerja dan Pengalaman Kerja Terhadap Motivasi Kerja Pegawai Balai Penyuluhan Pertanian Lubuk Tarok Kabupaten Sijunjung - Mutia Ramadhani; Heliyani Heliyani (Universitas Batanghari, 2022)
This study aims to see the effect of (1) organizational culture on the performance of BPP Agriculture Lubuk Tarok Sijunjung employees (2) Job satisfaction on the performance of Lubuk Tarok Agricultural BPP employees, Sijunjung Regency (3) Work experience on the performance of Lubuk Tarok Agricultural BPP employees, Sijunjung Regency (4 ) Organizational culture, job satisfaction and work experience jointly affect the performance of BPP Agriculture Lubuk Tarok employees, Sijunjung Regency. The population in this study were all employees of Agricultural BPP Lubuk Tarok, Sijunjung Regency as many as 95 people. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. The results of this study indicate that (1) Organizational culture has a positive significant effect on the performance of BPP Agriculture Lubuk Tarok Sijunjung Regency employees (2) Job satisfaction has a positive influence on the performance of Lubuk Tarok Agricultural BPP employees, Sijunjung Regency (3) Work experience has a significant influence positive effect on the performance of BPP Agriculture Lubuk Tarok Sijunjung Regency employees (4) Organizational culture, job satisfaction and work experience together have a positive effect on the performance of Lubuk Tarok Agricultural BPP employees, Sijunjung Regency.